Participatory democracy and civil society: Transforming societal decision-making in the information age - Keskinen, Auli (Politologija, 1997)
In this article, Auli Keskinen, Futures Researcher for Finland Futures Research Centre, and Director of Research and Development departments at the Ministry of the Environment, Finland, discusses various points of view concerning the period of current global social transition and the coming of the information age. Author characterises both of them by an unprecedented global telecommunications and information networks explosion.Author propounds a postulate that our position is such that the rapid diffusion of computers and connected networks of electronic means, the information and communications technology (ICT) will have even more profound impact than before on various social phenomena such as, author enlists, work, entertainment, business, education and, most important of all, democracy - how it is understood, exercised and developed. What is ready to be born, then, she claims, is "teledemocracy" - a new form of direct democracy promoted by the ICT and Information Networks.In addition, author enlists three important developments and trends concerning the current status of representative democracy vis-a-vis the citizen. First, A. Keskinen insists that nowadays democracy is in crisis; due to the expanding access to ICT and, henceforth, vast amount of information, large segments of the population are now and more so, in the future able to form personal educated opinions on common issues; second, having grown impatient with the narrow-aiming policies of the government, in modern societies many people want to shift from being "the governed" into having "self-government". This point emphasises that people do want to become actors in society instead of being mere subordinates. Third, Information Networks can act as an effective tool to enhance and reformulate, revise, the ways and ideas how democracy will, ought or should be developed and executed in societies. These three requisites help identify the growing importance of the ICT and other Informational Networks which, via revising global social developments, term the new body and the essence of another social phenomenon - democracy, or, eventually, teledemocracy. Furthermore, author sets to analyse "different ways", "different truths" which could work for the development of teledemocracy, the type of democracy, which, given the usage of ICT as a tool, might hand the reins of self-governance over to society, introduce the right of direct participation of every citizen in political agenda-setting, hence help transform a modern representative democracy into the participatory democracy.A. Keskinen, having argued for the creation of a decision-making Network, argues for the adoption of enhancing the publicity and promoting a suitable setting for the dialogue to develop; therefore, she describes different methods which work for the later conclusion that teledemocracy is a type, a model, of deliberative democracy. A. Keskinen argues that there can hardly be pure and discernible criteria which could acknowledge the existence of teledemocracy, it is rather a mixture, she argues, of different strategies, different models which by themselves do not strictly belong to one of the models.In conclusion, in the face of the growing dissatisfaction with the policymakers, the biased and trivial company of few, the forth-appearing inclination to assure "self-governance" and independence, not remaining meek "governed", usage of ICT and Information Networks in developing a fruitful basement for societal dialogue, global explosion of telecommunications and information networks, A. Keskinen asserts, work for the establishment of a new form of direct democracy - teledemocracy. Charts, depiction of different models of democracy, and so forth, may serve a favourable ground for further studies in this area. However, this is a rather hypothetical analysis of issues relevant to not so much contemporary life but moreover depicting certain trends in technological development which might soon even influence such social phenomenon like democracy and even synthesise a new type of it. This is truly an interesting futurist study.
Keywords: -